Patient and Nurse Perspectives on Hybrid Care Models: A Qualitative Study of Telehealth Integration in Nursing Specialty Services - Aiydah Aiyed A Aldhafeeri, Amani Hamdan Hadi Aldhafeeri, Al-HanoufJulaidanQunafid Al-Dhafiri, Reham Khalaf Abdullah Alenezi, Shama Abdullah Ali Alsafairi; Majdah Alshawi Samdan Alruwaili, Abeer Saad Alshammary, Ashwaq Inad Alanazi, Amwag Marwah Marji Al-Dhafiri, Samar Ali Adhman Aljameeli (Journal of International Crisis and Risk Communication Research, 2024)
The integration of telehealth into nursing specialty services has gained significant attention in recent years, particularly in the context of the COVID-19 pandemic. This qualitative study aimed to explore patient and nurse perspectives on hybrid care models that combine in-person and telehealth services in nursing specialty care. Semi-structured interviews were conducted with 20 patients and 20 nurses from various nursing specialty services in Saudi Arabia. Thematic analysis of the interview data revealed four main themes: (1) the benefits and challenges of telehealth integration, (2) the importance of patient-centered care and communication, (3) the need for training and support for telehealth adoption, and (4) the potential for telehealth to enhance access and continuity of care. Patients and nurses recognized the convenience and flexibility offered by telehealth, but also highlighted concerns related to technical issues, privacy, and the quality of virtual interactions. They emphasized the importance of maintaining a patient-centered approach and effective communication in hybrid care models. Additionally, participants identified the need for adequate training and support for both patients and nurses to facilitate the successful integration of telehealth into nursing specialty services. The findings suggest that hybrid care models have the potential to enhance access and continuity of care in nursing specialty services, but require careful planning, implementation, and evaluation to ensure their effectiveness and acceptability to patients and nurses.